2012
DOI: 10.1111/j.1582-4934.2012.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Transendocardial cell injection is not superior to intracoronary infusion in a porcine model of ischaemic cardiomyopathy: a study on delivery efficiency

Abstract: Stem cell therapy is a new strategy for chronic ischaemic heart disease in patients. However, no consensus exists on the most optimal delivery strategy. This randomized study was designed to assess cell delivery efficiency of three clinically relevant strategies: intracoronary (IC) and transendocardial (TE) using electromechanical mapping guidance (NOGA) compared to surgical delivery in a chronic pig model of ischaemic cardiomyopathy. Twenty-four animals underwent delivery of 107 autologous Indium-oxine-labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 31 publications
(47 reference statements)
1
49
1
Order By: Relevance
“…The MI was induced as previously described [17]. Briefly, animals were sedated and general anesthesia was maintained by continuous infusion of midazolam (0.7 mg/kg/hr), sufentanil citrate (6 μg/kg/hr) and pancurorium bromide (0.1 mg/kg/hr) via the canulated ear vein.…”
Section: Methodsmentioning
confidence: 99%
“…The MI was induced as previously described [17]. Briefly, animals were sedated and general anesthesia was maintained by continuous infusion of midazolam (0.7 mg/kg/hr), sufentanil citrate (6 μg/kg/hr) and pancurorium bromide (0.1 mg/kg/hr) via the canulated ear vein.…”
Section: Methodsmentioning
confidence: 99%
“…Pressure-volume loops were measured using a 7-F conductance catheter, as previously described [20]. Briefly, LV pressure and volumes were measured and stored using a Leycom CFL-512 (CD Leycom, Zoetermeer, the Netherlands).…”
Section: Pressure-volume Loop Analysismentioning
confidence: 99%
“…Percutaneous coronary cell delivery is less invasive and demonstrates the most frequent application route in the clinical setting. Until now, controversy existed about whether intramyocardial or intracoronary administration was superior [2628]. Some studies have shown that systemic intravenous administration of cells could hardly home to the heart because of the pulmonary first‐pass effect.…”
Section: Discussionmentioning
confidence: 99%